2008
DOI: 10.1017/s0007114508135814
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-standardised lean and fat indices derived from bioelectrical impedance analysis for ages 7–11 years: functional associations with cardio-respiratory fitness and grip strength

Abstract: Indices for lean and fat mass adjusted for height derived from bioelectrical impedance for children aged 7 years have been published previously and their usefulness in the clinical assessment of undernutrition has been demonstrated. However, there is a need for norms that cover a wider age range and to explore their functional significance. The aim of the present study is to derive lean and fat indices for children aged 7 -11 years and investigate associations with objective measures of cardio-respiratory fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 16 publications
3
38
1
1
Order By: Relevance
“…There was no evidence that these children had lost lean mass during the weaning process, and this would be unlikely in view of their sufficient fat stores. A more likely explanation is that their lean mass was a longstanding feature, which is in keeping with other studies which have found low lean mass in nutritionally stable children with physical disability 21 23. Whether this reflects earlier undernutrition or just the children's underlying syndromes is not clear, but in these circumstances aiming to attain an average BMI may well result in overfeeding and loss of appetite.…”
Section: Discussionsupporting
confidence: 64%
“…There was no evidence that these children had lost lean mass during the weaning process, and this would be unlikely in view of their sufficient fat stores. A more likely explanation is that their lean mass was a longstanding feature, which is in keeping with other studies which have found low lean mass in nutritionally stable children with physical disability 21 23. Whether this reflects earlier undernutrition or just the children's underlying syndromes is not clear, but in these circumstances aiming to attain an average BMI may well result in overfeeding and loss of appetite.…”
Section: Discussionsupporting
confidence: 64%
“…yCompared with ALSPAC (Avon Longitudinal Study of Parents and Children) reference (19) . JInternally standardised.…”
Section: Discussionmentioning
confidence: 99%
“…We observed positive correlations between body mass and strength in accordance with others. 31 However, a more accurate estimate of lean mass might afford a better understanding of this finding. The association between height and strength in children, which we also observed in our samples, is an important phenomenon and one that is thought to explain much of the differences in strength between similarly aged children.…”
Section: Strength Differences In Children Were Likely Maturitydependentmentioning
confidence: 99%